EFEKTIFITASPELAYANANPUBLIK DIKECAMATAN SAMARINDA KOTA DI SAMARINDA - Ahmad Jubaidi (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2018)
The purpose of this study is to determine the effectiveness of KK, KTP, and AK services in Samarinda Kota sub district and its factors influencing the effectiveness of KK, KTP, AKservices.The research used field research method which gives an overview on the effectiveness of KK, KTP, and AK services in Samarinda Kota sub district. Data collection techniques use observation techniques, interviews, and media questionnaires by selecting informants who play a role and are involved technically and functionally in service delivery to the community. The data obtained are then analyzed qualitatively and supported by quantitative data.The results showed that service implementation in Samarinda Kota sub-district, especially in the field of population administration and civil registration is done in accordance with existing mechanism and regulation which have been determined by seeing some service indicator such as simplicity is in very safe category with 6.67% and certainty of service procedure and tariff cost are in accordance with the value of 88.33% and 70% respectively, the security and convenience of facilities and infrastructure are in safe and comfortable category with 65% and 73.33% respectively, openness about the ease of obtaining information and provisions services in the categories easy and explained if requested with the value of 71.67% and 63.33% respectively, economical about the cost of KK rates, ID cards, AK category Rp 10,000 - Rp 15,000, equitable fairness with a value of 60%, the timeliness is in category 1 - 2 days, and the efficiency is an exact category with a value of 80%.  And the factors that affect the service is the resources apparatus, facilities and infrastructure, and public awareness. Keywords: Effectiveness, Public Service